Non-pharmacological interventions a feasible option for addressing dementia-related sleep problems in the context of family care - Gibson R; Dowell A; Jones L; Gander P (BioMed Central Ltd, 2021)
Background Sleep disturbances are challenging symptoms associated with mild cognitive impairment or dementia (MCIoD). This study assessed the feasibility of sleep monitoring and non-pharmacological interventions to improve the sleep of New Zealanders with MCIoD and their family carers. Methods A 5-week multi-modal intervention consisting of timed bright light therapy, physical activity, and sleep education was piloted. Sleep was monitored for a week at baseline and conclusion of the trial using actigraphy, diaries, and questionnaires alongside additional health and wellbeing information concerning both care recipients and carers. Results Fifteen pairs participated, 9 completed the trial. Patterns of attrition and participant feedback are discussed. Case studies showed that six of the care recipients had minor improvements to sleep efficiency. Some also had improved subjective sleep ratings and quality of life. Changes did not clearly translate to family carers. However, five of them also showed some improvements in sleep status and mental health. Health deterioration of care recipients may mask the effects of the intervention. Conclusions It is feasible to use non-pharmacological sleep interventions for people with MCIoD and their family carers. Given the limited treatment options, further consideration of such interventions in future research and clinical practice is warranted. Trial registration As this study was to assess the feasibility of proposed methods, it was an observational study without case-control groups nor a medical-based intervention, clinical registration was not required. A future full version of the trial would be registered with the Australian New Zealand Clinical Trails Registry.
Keywords: Actigraphy; Ageing; Caregiving; Dementia; Non-pharmacological interventions; Sleep problems